Systematic Review and Meta-Analysis: Seroprevalence, Vaccination Rates, and Response for Hepatitis A in Inflammatory Bowel Disease - Jena, Anuraag; Singh, Anupam Kumar; Neelam, Pardhu B.; Mohindra, Ritin; Kumar-M, Praveen; Mishra, Shubhra; Patil, Amol; Suri, Vikas; Sharma, Vishal (Journal of Gastrointestinal Infections, 2022)
Introduction Guidelines recommend hepatitis A virus (HAV) vaccination in individuals with inflammatory bowel disease (IBD). We performed a systematic review to inform the clinical practice regarding this guidance.Methods After a PubMed and Embase search, duplicates were removed and the remaining titles screened for studies reporting relevant outcomes. Pooled seroprevalence rates for HAV, pooled vaccination rates, and pooled seroconversion rates were calculated. We also calculated pooled relative risk of seroprevalence for HAV among IBD and control population. Heterogeneity was investigated using subgroup analysis.Results The pooled seroprevalence of HAV antibodies in patients with IBD (14 studies, 2,370 patients) was 0.36 (95% confidence interval [CI]: 0.22–0.53, I2 = 95%). On comparing the seroprevalence of HAV in IBD with controls (4 studies), the pooled relative risk was not different between the two (0.94, 95% CI: 0.66–1.34, I2 = 76%). The pooled seroconversion rate after two doses of HAV vaccination (5 studies, 221 patients) was 0.93 (95% CI: 0.88–0.96, I2 = 0%). Three studies (104 patients) reported on the seroconversion after a single dose of HAV vaccination and the pooled seroconversion rate was 0.47 (95% CI: 0.35–0.59, I2 = 20%). The pooled vaccination rate for hepatitis A among patients with IBD (18 studies, 9,521 patients) was 0.21 (95% CI: 0.14–0.30, I2 = 99%).Conclusion Hepatitis A vaccine has good immunogenicity in patients with IBD. The decision to routinely vaccinate IBD patients may be made in light of underlying seroprevalence of HAV.
Keywords: hepatitis A; ulcerative colitis; Crohn's disease; inflammatory bowel disease; immunization; vaccine